Pelatihan Kewirausahaan Bagi Masyarakat Gampong untuk Mengembangkan Usaha Mikro di Kecamatan Peureulak - Maknuni, Jauharil; Wiriani, Erni; Zulkarnaini (BA: Jurnal Pengabdian kepada Masyarakat, 2023)
Entrepreneurship training for village communities in Peureulak District aims to help improve the skills and knowledge of residents in developing their micro-enterprises. Entrepreneurship training methods for village communities in Peureulak District can be carried out using several methods, including: 1), Lectures, 2) Group discussions, 3) Case studies, 4) Exercises, 5) Field visits. This training will discuss various important topics in starting and managing a micro business, such as how to make business planning, financial management, marketing and operations effective and efficient. The trainees will learn how to make a good business plan, including how to do market analysis and determine the right marketing strategy. They will also learn about financial management, including how to manage cash flow and create simple financial reports. In addition, the training will also discuss business operations, such as inventory management, production and customer service. Participants will learn strategies to maximize efficiency and improve the quality of the products and services they offer. After attending the training the participants can apply the knowledge they have learned to develop their micro business and increase their income. Thus this training can help improve the economic welfare of entrepreneurship training participants for village residents in the Peureulak District through the development of quality micro-enterprises